KESADARAN MASYARAKAT DALAM MENGGUNAKAN MEDIA SOSIAL DI DESA SAKRA: Public Awareness In Using Social Media In Sakra Village - Mira Purnia Ningsih (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Social media has become a necessity for most people. While social media use is not prohibited in Indonesia, people must be aware of its negative impacts. The purpose of this study was to determine public awareness of social media use in Sakra Village. This research is a survey research with a qualitative approach related to public awareness in using social media in Sakra Village. The results show that media use in Sakra Village has grown rapidly, particularly through social media. However, public awareness of media use varies and is not yet fully optimal. Low media literacy makes people susceptible to misinformation. Media awareness is influenced by various factors, such as education, age, social environment, and the role of the village government